John B. Smith correspondence - Smith, John B., active 1861.
ALS (1861 September 28) from Smith to Robert M. Patterson of Washington County, Pa., threatening him with blackmail and death if Patterson does not deliver $500 to Smith.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Patterson, Robert M. -- Correspondence; Extortion; Washington County (Pa.) -- History